Preparing Bilingual NinDigging up EFL Teacher’s Instructional Strategies to Create Sustainable Communicative Language Teaching (CLT) Environment - Noviani Nurjannah; Gin Gin Gustine; Ahmad Bukhori Muslim (Al-Madrasah: Jurnal Pendidikan Madrasah Ibtidaiyah, 2023)
Pervasive power of English communication has led several reforms in education system for nations all over the world, no exception Indonesia. The reforms cover the integration of English communication skill as life skill into curriculum which familiarly has been introduced as twenty century skills called as 4Cs skills integration. This study revealed the EFL teacher’s instructional strategies in creating communicative teaching and learning by using conceptual framework of Communicative Language Teaching (CLT). Case study qualitative research design is employed to answer research questions. The respondents are bilingual ninth grade teacher and school pricipal. To collect data, this study uses semi structured interview, observation and document analysis. The interview was aimed at knowing the EFL teacher’s instructional strategies in creating communicative teaching and learning environment. The collected data were then supported by observation and document analysis. The result of this study revealed that EFL teacher uses several instructional strategies to create communicative teaching and learning environment including role play, games, map-reading, surveys, presentation and the other kinds of classroom activities.